Асимметрия структуры поверхностного сосудистого русла мозжечка человека - Степаненко, Олександр Юрійович; Степаненко, Александр Юрьевич; Stepanenko, Oleksandr (ГУ «Днепропетровская медицинская академия Министерства здравоохранения Украины», 2017)
Мета дослідження - встановити відмінності структури поверхневої судинної мережі верхньої і нижньої поверхонь мозочка і їх зв'язок з величиною і формою мозочка. У пропорційних за формою мозочків значення фрактального індексу верхньої і нижньої поверхні збігаються практично функціонально, і маса мозочка не впливає на це співвідношення. Відхилення форми мозочка від пропорційної збільшує відмінності структури судинної мережі на верхній і нижній поверхні. Ширина мозочка впливає на структуру судинної мережі на обох його поверхнях. Довжина мозочка більше впливає на структуру судинної мережі нижньої поверхні, ніж верхньої. Висота однаково впливає на обидві поверхні мозочка. Цель исследования – установить различия структуры поверхностной сосудистой сети верхней и нижней поверхностей мозжечка и их связь с величиной и формой мозжечка. У пропорциональных по форме мозжечков значения фрактального индекса верхней и нижней поверхности совпадают практически функционально, и масса мозжечка не влияет на это соотношение. Отклонение формы мозжечка от пропорциональной увеличивает различия структуры сосудистой сети на верхней и нижней поверхности. Ширина мозжечка влияет на структуру сосудистой сети на обеих его поверхностях. Длина мозжечка больше влияет на структуру сосудистой сети нижней поверхности, чем верхней. Высота одинаково влияет на обе поверхности мозжечка. Background. Development of methods for diagnosing the risk of developing acute cerebral circulation disorders and their prevention requires a deep understanding of тhe patterns of the structure of the vascular networks of different departments of the central nervous system. Objective. To establish differences in the structure of the superficial vascular network of the upper and lower surfaces of the cerebellum and their relationship to the size and shape of the cerebellum. Methods. The study was conducted on 100 cerebellums of people of both sexes, who died of causes unrelated to brain pathology (20–95 years old). The morphometric study was carried out by the method of fractal analysis. The dependence of the fractal index values on the mass and linear dimensions of the cerebellum was studied by statistical methods: regression andcorrelation analysis. Results. In cerebellum with proportional shape the values of the fractal index of the upper and lower surfaces coincide practically functionally, and the mass of the cerebellum does not affect this ratio. The deviation of the shape of the cerebellum from proportional increases the differences in the structure of the vasculature on the upper and lower surface. The width of the cerebellum influences the structure of the vasculature on both its surfaces. The length of the cerebellum affects the structure of the vascular network of the lower surface more than the upper one. The height affects both surfaces of the cerebellum equally. Conclusions. The use of fractal analysis as a morphometric method and a fractal index as a morphometric criterion makes it possible to objectively characterize the structure of the cerebellar superficial vascular bed.
Keywords: людина; мозочок; судини; індивідуальна мінливість; человек; мозжечок; сосуды; индивидуальная изменчивость; man; cerebellum; vessels; individual variability